Incidence and Distinct Features of Immune Checkpoint Inhibitor-Related Myositis From Idiopathic Inflammatory Myositis: A Single-Center Experience With Systematic Literature Review and Meta-Analysis - Hamada, Naoki; Maeda, Ayaka; Takase-Minegishi, Kaoru; Kirino, Yohei; Sugiyama, Yumiko; Namkoong, Ho; Horita, Nobuyuki; Yoshimi, Ryusuke; Nakajima, Hideaki; , YCU irAE Working Group; Hamada, Naoki; Kirino, Yohei; et al. (Frontiers in Immunology, 2021)
Immune checkpoint inhibitor (ICI)-related myositis is a rare, potentially fatal condition that warrants further studies. Its incidence, clinical features, and prognosis remain poorly understood. To address these gaps, we conducted a systematic review and meta-analysis to evaluate the risk of myositis associated with ICI for solid tumors by analyzing phase III randomized controlled trials of anti-programmed death-1/ligand-1 (PD-1/PD-L1) and anti-cytotoxic T-lymphocyte antigen-4 (CTLA-4). To complement this analysis with clinical data, we evaluated published ICI case reports along with cases from our institutional registry. This registry comprised 422 patients treated with ICIs alone or in combination from September 2014 to June 2021. The analysis revealed an incidence of ICI-related myositis in 6,838 patients in 18 randomized controlled trials of 0.38% (odds ratio 1.96; 95% confidence interval 1.02–3.75) for patients receiving ICIs compared with controls. Detailed analysis of 88 cases from the literature search and our registry showed that myositis induced by PD-1 inhibitors was more frequent than that induced by anti-CTLA-4 agents, revealing a clinically diverse trend including myasthenia gravis and myocarditis. Importantly, having ptosis at the time of onset was significantly associated with the development of concomitant myocarditis (odds ratio 3.81; 95% CI 1.48–9.83), which is associated with poor prognosis. Regarding treatment, most patients received glucocorticoids, and some received immunosuppressants. Our study revealed the incidence of ICI-mediated myositis and the clinical features of myocarditis, highlighting the need for recognition and early intervention.